2020
DOI: 10.3390/ijms21176450
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thiocyanate in Modulating Myeloperoxidase Activity during Disease

Abstract: Thiocyanate (SCN−) is a pseudohalide anion omnipresent across mammals and is particularly concentrated in secretions within the oral cavity, digestive tract and airway. Thiocyanate can outcompete chlorine anions and other halides (F−, Br−, I−) as substrates for myeloperoxidase by undergoing two-electron oxidation with hydrogen peroxide. This forms their respective hypohalous acids (HOX where X− = halides) and in the case of thiocyanate, hypothiocyanous acid (HOSCN), which is also a bactericidal oxidative speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 131 publications
(162 reference statements)
0
8
0
Order By: Relevance
“…SCN − , the precursor of HOSCN, is found in many human secretions, with the highest reported concentrations (from 0.01 to 2 mM) in the lungs and oral cavity ( 13 ). The levels of SCN − in human fluids are dependent on diet and can be increased by consuming brassica vegetables such as broccoli or Brussels sprouts ( 14 ), as well as being present in much higher concentrations in the plasma of smokers (up to 3 mM) ( 13 , 15 ). In mammalian tissues, accumulation of SCN − acts as a chemical shield against damaging hypohalous acids ( 16 ).…”
mentioning
confidence: 99%
“…SCN − , the precursor of HOSCN, is found in many human secretions, with the highest reported concentrations (from 0.01 to 2 mM) in the lungs and oral cavity ( 13 ). The levels of SCN − in human fluids are dependent on diet and can be increased by consuming brassica vegetables such as broccoli or Brussels sprouts ( 14 ), as well as being present in much higher concentrations in the plasma of smokers (up to 3 mM) ( 13 , 15 ). In mammalian tissues, accumulation of SCN − acts as a chemical shield against damaging hypohalous acids ( 16 ).…”
mentioning
confidence: 99%
“…Secretion of SCN − (and also I − ) from epithelial cells at the apical site occurs through several mechanisms [ 82 ]. The main focus is usually directed on two anion channels, cystic fibrosis trans-membrane conductance regulator (CFTR) and pendrin.…”
Section: The Lactoperoxidase-hydrogen Peroxide-thiocyanate System In Mucous Fluids and Secretionsmentioning
confidence: 99%
“…There is significant variation in terms of SCN − levels amongst such fluids. In a recent review, saliva was reported to exhibit the highest SCN − levels, with a range from 0.5 up to 2 mM, whereas plasma or urine SCN − concentrations were detected at the µM degree [41]. The remarkable difference of SCN − levels in saliva from those in others may be due to the presence of LPO along with other antimicrobial defenses in saliva [42].…”
Section: Innate Antioxidant Defense Systems In Periodontal Tissuesmentioning
confidence: 99%